Physicochemical and Functional Characterization of Egg Replacer Based on Protein Isolate, Starch, and Hydrocolloid - Nursya Sitorus; Elisa Julianti; Ridwansyah Ridwansyah (Universitas Sumatera Utara, 2015)
The research was aimed to study the physicochemical and functional characteristics of egg replacer based on soy protein isolate, whey protein isolate, corn starch, guar gum, and xanthan gum. The research had been performed using non factorial completely randomized design with 12 levels and 3 repetition. Ratio of the threatment of soy protein isolate, corn starch, and guar gum (E1 = 70% : 29,5% : 0,5% ; E2 = 70% : 29,0% : 1,0% ; E3 = 70% : 28,5% : 1,5%), soy protein isolate, corn starch, and xanthan gum (E4 = 70% : 29,5% : 0,5% ; E5 = 70% : 29,0% : 1,0% ; E6 = 70% : 28,5% : 1,5%), whey protein isolate, corn starch, and guar gum (E7 = 70% : 29,5% : 0,5% ; E8 = 70% : 29,0% : 1,0% ; E9 = 70% : 28,5% : 1,5%), whey protein isolate, corn starch, and xanthan gum (E10 = 70% : 29,5% : 0,5% ; E11 = 70% : 29,0% : 1,0% ; E12 = 70% : 28,5% : 1,5%), and whole egg powder. Parameters analyzed were water content, ash content, protein content, fat content, carbohydrate content, foam capacity, foam stability, emulsion capacity and activity, color, and density.The results showed that the egg replacer based on with soy protein isolate, whey protein isolate, corn starch, and hydrocolloid (guar gum, and xanthan gum) had the different the physicochemical and functional characteristics. Egg replacer had the different physicochemical and functional characteristics with control. The egg replacer from soy protein isolate, corn starch and xantan gum with the ratio of 70%:29,5%:0,5% had the physicochemical and functional properties that comparable than those of egg flour. Keywords:, Corn starch, hydrocolloid, protein isolate